Capillariid nematodes in Brazilian turkeys, Meleagris gallopavo (Galliformes, Phasianidae): pathology induced by Baruscapillaria obsignata and Eucoleus annulatus (Trichinelloidea, Capillariidae) - Roberto Magalhães Pinto; Beatriz Brener; Rogério Tortelly; Rodrigo Caldas Menezes; Luís Cláudio Muniz-Pereira (Memorias do Instituto Oswaldo Cruz, 2008)
The pathology induced in turkeys (Meleagris gallopavo) by two capillariid nematodes, Baruscapillaria obsignata and Eucoleus annulatus is described together with data on prevalences, mean infection and range of worm burdens. B. obsignata occurred with a prevalence of 72.5% in the 40 examined hosts in a range of 2-461 nematodes and a mean intensity of 68.6, whereas E. annulatus was present in 2.5% of the animals, with a total amount of five recovered parasites. Gross lesions were not observed in the parasitized birds. Lesions due to B. obsignata mainly consisted of the thickening of intestinal villi with a mild mixed inflammatory infiltrate with the presence of mononuclear cells and heterophils. The lesions induced by E. annulatus were represented by foci of inflammatory infiltrate with heterophils in the crop epithelium and esophagus of a single infected female. These are the first pathological findings related to the presence of capillariid worms in turkeys to be reported in Brazil so far. Capillaria anatis, although present, was not pathogenic to the investigated turkeys.